2021
DOI: 10.1007/s00234-021-02825-5
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging characteristics of uveal melanoma with histopathological validation

Abstract: Purpose To evaluate the magnetic resonance imaging (MRI) characteristics of uveal melanoma (UM), to compare them with fundoscopy and ultrasound (US), and to validate them with histopathology. Methods MR images from 42 UM were compared with US and fundoscopy, and on 14 enucleated cases with histopathology. Results A significant relationship between the signal intensity on T1 and pigmentation on histopathology was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(82 citation statements)
references
References 44 publications
8
73
1
Order By: Relevance
“…The mean ADC of ocular melanomas we measured in the present cohort, in both the irradiated and the control group (0.78 × 10 −3 mm 2 /s and 0.92 × 10 −3 mm 2 /s respectively) is lower than that reported in a recently published study by Ferreira et al [ 41 ] but is only partially inconsistent with this latter. In our opinion such a low ADC value found in the control group could probably be related to our study cohort (large tumors needing enucleation); it is, in fact, closer to that reported by Erb-Eigner et al [ 61 ] in whose study uveal melanomas had a mean diameter of 14 mm (very similar to our).…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…The mean ADC of ocular melanomas we measured in the present cohort, in both the irradiated and the control group (0.78 × 10 −3 mm 2 /s and 0.92 × 10 −3 mm 2 /s respectively) is lower than that reported in a recently published study by Ferreira et al [ 41 ] but is only partially inconsistent with this latter. In our opinion such a low ADC value found in the control group could probably be related to our study cohort (large tumors needing enucleation); it is, in fact, closer to that reported by Erb-Eigner et al [ 61 ] in whose study uveal melanomas had a mean diameter of 14 mm (very similar to our).…”
Section: Discussioncontrasting
confidence: 97%
“…In our opinion such a low ADC value found in the control group could probably be related to our study cohort (large tumors needing enucleation); it is, in fact, closer to that reported by Erb-Eigner et al [ 61 ] in whose study uveal melanomas had a mean diameter of 14 mm (very similar to our). In line with this, also Ferreira et al found uveal melanomas with larger tumor prominence having lower ADC values [ 41 ]. The even lower ADC value we found in the irradiated group could be associated with tumor aggressiveness since these uveal melanomas represent tumor regrowth (recurrence), but honestly, the number of available measurements (only four) is too small to make any assumptions.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations